2020
DOI: 10.1038/s41598-020-58807-9
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported sleep disturbance in Crohn’s disease is not confirmed by objective sleep measures

Abstract: Sleep disturbance and fatigue are commonly reported among patients with Crohn's disease (CD). In this prospective study, we aimed to define sleep quality in CD patients at various disease activity states and compare to healthy controls using objective and subjective measures. A prospective observational cohort study of CD patients seen at a tertiary academic inflammatory bowel diseases (IBD) clinic was compared to healthy volunteers. CD activity was assessed using the Harvey-Bradshaw Index (HBI). Sleep quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Iskandar et al did not notice the difference in ESS between CD and HC, but patients with active disease had higher scores than in the remission. There were also no differences in the results of actigraphy and urine melatonin levels between CD and controls [27]. In another study, there were no differences in ESS depending on the severity of the disease, while actigraphy has shown decreased sleep efficiency in moderate and severe CD group compared to patients in remission [34].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Iskandar et al did not notice the difference in ESS between CD and HC, but patients with active disease had higher scores than in the remission. There were also no differences in the results of actigraphy and urine melatonin levels between CD and controls [27]. In another study, there were no differences in ESS depending on the severity of the disease, while actigraphy has shown decreased sleep efficiency in moderate and severe CD group compared to patients in remission [34].…”
Section: Discussionmentioning
confidence: 89%
“…The problem of disordered sleep in immune diseases has been recently widely studied [14,16,27,28]. To date, only a few studies have been published assessing sleep quality among IBD patients using mainly PSQI [14,29].…”
Section: Discussionmentioning
confidence: 99%
“…An improvement in sleep and mood quality was observed in patients responding to anti-TNF-α or vedolizumab 102 . Conversely, the association between IBD and sleep disorders has been questioned by a study objectively measuring sleep parameters by actigraphy, urine melatonin metabolites and two different sleep quality indexes 103 . These data are in line with other reports suggesting the importance of IBS-like symptoms on the sleep quality of IBD patients in clinical remission 104 .…”
Section: Digestive Diseases and Sleep Disordersmentioning
confidence: 99%
“…2 and 3). [7,[20][21][22][23]. A cross-sectional study among the general population (n = 3228) showed that those with poor sleep quality were more likely to experience gastrointestinal symptoms [20].…”
Section: Sleep Quality Quantity and Gastrointestinal Problems Characteristicsmentioning
confidence: 99%